2015
DOI: 10.1038/srep10520
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social support during pregnancy and postpartum depressive state: a prospective cohort study

Abstract: Although the association between social support and postpartum depression has been previously investigated, its causal relationship remains unclear. Therefore, we examined prospectively whether social support during pregnancy affected postpartum depression. Social support and depressive symptoms were assessed by Japanese version of Social Support Questionnaire (J-SSQ) and Edinburgh Postnatal Depression Scale (EPDS), among 877 pregnant women in early pregnancy and at one month postpartum. First, J-SSQ was stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 48 publications
8
78
1
Order By: Relevance
“…This is consistent with previous research which suggested a greater number of support persons in pregnancy reduced postpartum depressive symptoms 14. Our study complements this finding as we considered social support to comprise the availability of different resources provided by support people, not only the number of people.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research which suggested a greater number of support persons in pregnancy reduced postpartum depressive symptoms 14. Our study complements this finding as we considered social support to comprise the availability of different resources provided by support people, not only the number of people.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with the results of many other studies like Giurgescu et al and Morikawa et al, they found that mothers who enjoyed adequate social support during pregnancy experienced have a healthier pregnancy compared to those who did not have (42,43). Family and husband support during pregnancy may effect on maternal and fetal health through unmeasured mediators such as improved maternal health behaviors (refraining from smoking and drinking, etc.…”
Section: Discussionsupporting
confidence: 82%
“…Social support as a protective and modifiable factor has been well investigated in relation to antepartum or postpartum depression. Some studies have demonstrated that poor social support during pregnancy is associated with an increased risk of antepartum (Aktas & Calik, ; Zeng, Cui, & Li, ) or postpartum depression (Morikawa et al., ), while others have investigated the significant relationship between social support and depression in the postpartum period (Leahy‐Warren, McCarthy, & Corcoran, ). However, few studies have considered changes in social support over the perinatal period and examined its relationship with depression at different times in the perinatal period.…”
Section: Introductionmentioning
confidence: 99%